Telovadba na delovnem mestu - Dišič, Mitja (Šport (Ljubljana), 2017)
The main characteristics of a modern lifestyle include insufficient physical activity, excessive and inappropriate nutrition as well as proneness to stressful situations. Although we seem to always be in a hurry, we actually spend a lot of time in forced postures, including sitting. We sit too much at home, in front of TV and the computer as well as in the car and at work. Many people spend many hours performing a sedentary job. The negative consequences of a sedentary life on health can be mitigated by suitable gymnastic exercises that are most effective if carried out every day at work. The article presents several sets of appropriate stretching and strengthening gymnastic exercises that can be performed during a 10-minute active break at work. The presented exercises are organised in sets of free-standing and wall exercises as well as elastic-, table- and chair-based exercises.
Keywords: active break; aktivni odmor; delovno mesto; krepilne gimnastične vaje; raztezne gimnastične vaje; sedenje; sitting; sport; strengthening gymnastic exercises; stretching gymnastic exercises; šport; work